AB1255-HPR Personal and Workplace Environmental Factors Associated with Reduced Worker Productivity Among People with Chronic Knee Pain. (9th June 2015) - Fransen, M.; Jan, S.; Mackey, M.G.; Heard, R.; Agaliotis, M.
Abstract : Background: Globally, with an ageing population, an increase in obesity and a tendency to delay retirement, the absolute numbers and prevalence of people affected by chronic knee pain in the workforce will increase 1 . A more recent review found strong evidence to indicate a positive association between knee pain or knee osteoarthritis and absenteeism from work. However, data were lacking to demonstrate a clear association with presenteeism 2 . Also few studies have examined, the influence of the physical or psychological workplace environment or individual or personal factors that may significant influences worker productivity or the decision making process of whether to go to or forgo work among people with knee pain 3 . Objectives: The aims of this study were to evaluate the burden of absenteeism, presenteeism and work transitions and explore the personal and workplace environmental risk factors associated with reduced worker productivity among people with chronic knee pain. Methods: A survey containing several validated measures of absenteeism, presenteeism and work transitions as well as individual, disease and work-related demographics was mailed to 496 people who had completed participation in the Long-term Evaluation of Glucosamine Sulfate (LEGS) study. Results: A total of 296 (60%) people provided a completed survey with 129 currently in paid employment. Only six (5%) reported absenteeism in the past two months, however 63 (49%) reported presenteeism over a seven day period and 31 (24%) reported making one or more work transitions in the last six months due to knee problems. In multivariate analysis, presenteeism was associated with moderate to severe knee pain (≥3/10) (odds ratio (OR) 2.77, 95% CI 1.30 – 5.8) and reporting problems with other joints (OR 2.32, 95% CI 1.04 – 5.17) while job instability reduced the likelihood (OR 0.40, 95% CI 0.19 – 0.86). Reporting one or more work transitions was associated with moderate to severe knee pain (OR 4.09, 95% CI 1.53 – 10.95), a high co-morbidity score (OR 4.44, 95% CI: 1.02 – 19.32) and low co-worker support (OR 2.79, 95% CI 1.04 – 7.46) while having an occupation involving sitting >30% of the working day reduced the likelihood (OR 0.35, 95% CI 0.12 – 0.97). Conclusions: This survey demonstrates the high prevalence of reduced worker productivity among people with chronic knee pain. Allowing access to sitting and promoting positive affiliations between co-workers are likely to provide an enabling workplace environment for these workers. References: Woolf AD, Pfleger B. Burden of major musculoskeletal conditions. Bull World Health Organ 2003;81(9):646-56. Agaliotis M, Mackey MG, Jan S, et al. Burden of reduced work productivity among people with chronic knee pain: a systematic review. Occupational and Environmental Medicine 2014. Tang K, Escorpizo R, Beaton DE, et al. Measuring the impact of arthritis on worker productivity: perspectives, methodologic issues, and contextual factors. J Rheumatol 2011;38(8):1776-90. Acknowledgements: We thank the LEGS participants for their contributions to our research. This work was supported by Arthritis Australia (The Kevin R James Grant) awarded to Ms Maria Agaliotis. Disclosure of Interest: None declared